2021
DOI: 10.1177/17470218211041953
|View full text |Cite
|
Sign up to set email alerts
|

Numeral order and the operationalization of the numerical system

Abstract: Recent years have witnessed an increase in research on how numeral ordering skills relate to children’s and adults’ mathematics achievement both cross-sectionally and longitudinally. Nonetheless, it remains unknown which core competency numeral ordering tasks measure, which cognitive mechanisms underlie performance on these tasks, and why numeral ordering skills relate to arithmetic and math achievement. In the current study, we focused on the processes underlying decision-making in the numeral order judgement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…On all other sequences, people may need to perform sequential comparisons to make order decisions, resulting in canonical distance effects (Lyons & Ansari, 2015;Lyons & Beilock, 2013). Together, the canonical and reverse distance effects observed in the order judgment task support the view that cardinal and ordinal processing of symbolic numerals are both involved, depending on the task demands and the extent to which adjacent sequences are present in the stimulus set (Dubinkina et al, 2021;Muñez et al, 2022;Vogel et al, 2021;Vos et al, 2017).…”
Section: Patterns Of Responses In Order Processing Tasksmentioning
confidence: 66%
See 1 more Smart Citation
“…On all other sequences, people may need to perform sequential comparisons to make order decisions, resulting in canonical distance effects (Lyons & Ansari, 2015;Lyons & Beilock, 2013). Together, the canonical and reverse distance effects observed in the order judgment task support the view that cardinal and ordinal processing of symbolic numerals are both involved, depending on the task demands and the extent to which adjacent sequences are present in the stimulus set (Dubinkina et al, 2021;Muñez et al, 2022;Vogel et al, 2021;Vos et al, 2017).…”
Section: Patterns Of Responses In Order Processing Tasksmentioning
confidence: 66%
“…If the sequence is shown for a brief time, they may also need to retain the sequence of digits in working memory. In summary, the literature suggests that order judgment performance is related to familiarity with previously learned sequences, knowledge of relative magnitude, and working memory (Devlin et al, 2022;Dubinkina et al, 2021;Finke et al, 2021;Muñez et al, 2022;Vogel et al, 2021;Vos et al, 2021).…”
Section: The Development Of Order Processingmentioning
confidence: 99%
“…In contrast, Orrantia et al (2019) highlight the extensive overlap between cardinal (number comparisons) and ordinal processing (order judgements) in adults’ arithmetic, suggesting that both processes draw on underlying symbolic magnitude associations. Other researchers have suggested that both familiarity and magnitude associations may influence performance on the order judgement task, depending on the task demands (e.g., stimulus characteristics; Vos et al, 2021) and individuals’ strategy use (Dubinkina et al, 2021; Muñez et al, 2021; Vogel et al, 2021; Vos et al, 2021). Extending the latter views, strong correlations between order judgements and arithmetic may reflect the extent to which individuals have developed an integrated knowledge system (Xu et al, 2019).…”
Section: Fundamental Numeracymentioning
confidence: 99%
“…Currently, the primary method of investigating the mechanisms underlying order processing involves using order judgement tasks in which participants have to Concepts of order: Why is ordinality processed slower and less accurately for non-consecutive sequences? classify sequences of digits (e.g., 1-2-3) as either correctly or incorrectly ordered (Dubinkina et al, 2023;Finke et al, 2021;Muñez et al, 2022;Wong et al, 2022). A noteworthy feature of these tasks is that they often produce a reverse distance effect whereby consecutive sequences (e.g., 1-2-3) are processed faster than non-consecutive sequences (e.g., 1-3-5; see Goffin & Ansari, 2016;Vogel et al, 2017Vogel et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%